-3(x+3)=3(x+1)-5

Simple and best practice solution for -3(x+3)=3(x+1)-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(x+3)=3(x+1)-5 equation:


Simplifying
-3(x + 3) = 3(x + 1) + -5

Reorder the terms:
-3(3 + x) = 3(x + 1) + -5
(3 * -3 + x * -3) = 3(x + 1) + -5
(-9 + -3x) = 3(x + 1) + -5

Reorder the terms:
-9 + -3x = 3(1 + x) + -5
-9 + -3x = (1 * 3 + x * 3) + -5
-9 + -3x = (3 + 3x) + -5

Reorder the terms:
-9 + -3x = 3 + -5 + 3x

Combine like terms: 3 + -5 = -2
-9 + -3x = -2 + 3x

Solving
-9 + -3x = -2 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-9 + -3x + -3x = -2 + 3x + -3x

Combine like terms: -3x + -3x = -6x
-9 + -6x = -2 + 3x + -3x

Combine like terms: 3x + -3x = 0
-9 + -6x = -2 + 0
-9 + -6x = -2

Add '9' to each side of the equation.
-9 + 9 + -6x = -2 + 9

Combine like terms: -9 + 9 = 0
0 + -6x = -2 + 9
-6x = -2 + 9

Combine like terms: -2 + 9 = 7
-6x = 7

Divide each side by '-6'.
x = -1.166666667

Simplifying
x = -1.166666667

See similar equations:

| 6(2x-5)=-3(7-3x)+3 | | 3x+35=10x-31 | | 3x^2+4y^2=121 | | (3z+6y)*(8y-4z)= | | 7x-9=(-9) | | (3x-5)+(5x+1)= | | -7/10m=-1327/24 | | 5(3-4x)+14x=7(2-5x) | | 9/5m-5/2m=1327/24 | | 3(6x-2)+4(1-5x)=x | | K/9-2=-11 | | -8.5-16=3*8.5+18+2*-8.5 | | ((1/21)x^(-1/21))(20-41x)=0 | | 27-9x=14 | | -4y-8=8y+100 | | -22-3x=-2x+x-3X | | -5=4x-3x | | 4w+5=5w-6 | | .5(2x+4)=3x-4 | | 4(8-x)=2x+16 | | -63+3y+8=2(5y-3)-7 | | 8n+11=10n-11 | | 2(x-5)=15x-4x | | x+(x*.0975)=4.21 | | .3x+1.4=4.2-.1x | | 4m+4=10m-62 | | -7/10m=-1324/24 | | 4+17n-3=9n+85-47 | | 100/900=85/x | | Y=-2x^3-2x^2+60x | | ax-2cx+4ay-8cy= | | 18-8-2=.5(18-2) |

Equations solver categories